HUBUNGAN PENGETAHUAN DAN TEMAN SEBAYA DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA - Metha Fahriani Metha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Teenagers are individuals who develop from the first time they show their secondary sexual signs until when they reach sexual maturity. According to SDKI in 2013, there are 38% of women and 12% of men have premarital sex under the age of 18. There are several factors that cause the delinquency of adolescents who engage in premarital sex among them is the lack of knowledge and peers. The aims of this study was to determine Relationship between Knowledge and Peers with Premarital Sexual Behavior on Adolescents at SMA Negeri 09 North Bengkulu. This study is quantitative research with survey analytic design that uses cross sectional approach. Population in this study were all students of class XI at SMAN 09 North Bengkulu with total of 125 people. Sampling technique in this study using Total Sampling technique. Data collection in this study used primary data and secondary data. Data analysis was performed univariate, bivariate by Chi-Square Test. The results of this study showed: There is significant relationship between knowledge with Premarital Sexual Behavior on Adolescents at SMA Negeri 09 North Bengkulu (x² =18,924, p=0,000), with moderate category of relationship (C=0,363); There is significant relationship between peers with Premarital Sexual Behavior on Adolescents at SMA Negeri 09 North Bengkulu, (x² =13,059, p=0,000), with moderate category of relationship (C=0,324). SMA Negeri 09 North Bengkuluis expected to be able to conduct health education about premarital sexual behavior. Keywords : Knowledge, Peers, Premarital Sexual Behavior